2019
DOI: 10.1111/jace.16483
|View full text |Cite
|
Sign up to set email alerts
|

Surface stabilities of 3C–SiC and H2O adsorption on the (110) surface

Abstract: First‐principles calculations and thermodynamics analyses were combined to study the surface stabilities of 3C–SiC and H2O adsorption on the (110) surface. The stoichiometric (110) surface was predicted to be generally the most stable. Only at the extremely C‐poor condition, the nonstoichiometric Si‐terminated (100) could become more energetically favored. The adsorption and dissociation of single H2O molecule on the 3C–SiC (110) were then comparatively investigated. Calculations show that H2O molecules prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…However, a recent study by Peng et al derived the thermodynamic phase diagram for various SiC facets, which revealed that the stoichiometric (110) surface is the most stable under the range of operating conditions relevant to our study. They found that water readily dissociates on the clean SiC (110) surface (Figure a), such that surface hydroxyl and hydrogen adsorb on Si and C surface sites, respectively, forming a hydrogen-bonded network on the surface . Accordingly, we employed a SiC (110) surface slab model with a dissociated water layer on both sides of the SiC (110) slab (Figure b).…”
Section: Methodsmentioning
confidence: 76%
See 4 more Smart Citations
“…However, a recent study by Peng et al derived the thermodynamic phase diagram for various SiC facets, which revealed that the stoichiometric (110) surface is the most stable under the range of operating conditions relevant to our study. They found that water readily dissociates on the clean SiC (110) surface (Figure a), such that surface hydroxyl and hydrogen adsorb on Si and C surface sites, respectively, forming a hydrogen-bonded network on the surface . Accordingly, we employed a SiC (110) surface slab model with a dissociated water layer on both sides of the SiC (110) slab (Figure b).…”
Section: Methodsmentioning
confidence: 76%
“…Earlier studies of HER on SiC employed SiC (111) and (100) surfaces that either were clean or covered with hydrogen . However, a recent study by Peng et al derived the thermodynamic phase diagram for various SiC facets, which revealed that the stoichiometric (110) surface is the most stable under the range of operating conditions relevant to our study. They found that water readily dissociates on the clean SiC (110) surface (Figure a), such that surface hydroxyl and hydrogen adsorb on Si and C surface sites, respectively, forming a hydrogen-bonded network on the surface .…”
Section: Methodsmentioning
confidence: 80%
See 3 more Smart Citations